Trend Analysis of Hepatic Infection in Pakistan - Shazia Irum, Shagufta Parveen, Muhammad Hassan Raza, Mariyam Haroon, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the trend analysis of hepatic infection within recent years in Pakistan. Study Design: Retrospective study. Place and Duration of Study: Department of Nephrology, Mayo Hospital, Lahore 1st July 2020 to 31st December 2020. Methodology: Five thousand patient’s files were screened. It was a hospital-based study analyzing the trend from outdoor or indoor registered patient’s files. The diagnosis of hepatitis infection was taken as confirmed on the basis of ELISA test positivity in situations where PCR results were not conducted. Comorbidities were also included in this study. Results: The mean age of hepatitis B patients was 27±2.5 years while of hepatitis C patients was 44±5.9 years. The prevalence of males was found higher as compared to the females. Different age groups were observed in HBV and HCV patients. HCV targeted higher age group patients. On the other hand, hepatitis B was onset and diagnosed at earlier ages. Conclusion: Due to upsurge in viral hepatitis within recent years, effective policies should be made to combat its adverse consequences. The hepatitis B prevalence increased up to 2.2% while hepatitis C increased up to 5% by year 2021.